Coordination‐Precipitation Synthesis of Metal Sulfide with Phase Transformation Enhanced Reactivity against Antibiotic‐Resistant Bacteria. (2nd February 2023) - Liu, Yuan; Wang, Xiaonan; Fan, Xiaowan; Ge, Mengyue; Fang, Ling; Yuan, Ye; Chen, Lei; Jiang, Jing; Cao, Anmin; Gao, Lizeng
Abstract: Given the challenge of bacterial resistance to antibiotics, there is an urgent need to develop alternative antibacterial agents. While some metal sulfides are promising candidates against bacterial resistance, their fundamental mechanism of action (MoA) remains unclear. Herein, a "coordination‐precipitation" method is developed for the synthesis of a metal sulfide library and the evaluation of antibacterial consistency. Employing ethylenediamine as a coordination agent and thioglycolic acid as a precipitation agent, 12 different metal sulfide nanocrystals following the same procedure are synthesized. Antibacterial assessment reveals that six metal sulfides with bactericidal potency perform a common feature of phase transformation. In particular, in the process of manganese sulfide (MnS) transformation to Mn3 O4, a highly reactive complex of high‐valance manganese (Mn 3+ ) and polysulfide (S3 2− ) accompanied by superoxide is sustainably generated, which synergistically induces bacterial death with a hallmark of lipid peroxidation (named liperoptosis) specifically toward Gram‐positive Staphylococcus aureus (S. aureus) . In addition, this MoA confers MnS with therapeutic effects superior to vancomycin in a methicillin‐resistant S. aureus ‐infected skin wound model. This study reveals the correlation between phase transformation and the antibacterial MoA of metal sulfides and provides a general fundamental to design a non‐antibiotic antibacterial candidate against bacterial resistance. Abstract : The coordination‐precipitation strategy is developed to synthesize metastable metal sulfides. As a representative, manganese sulfide exhibits selective antibacterial activity to induce methicillin‐resistant Staphylococcus aureus liperoptosis in vitro and in vivo through phase transformation‐mediated release of a manganese (Mn 3+ ) and polysulfide bactericidal complex. The unique antibacterial mechanism will facilitate the development of metal sulfide‐based antibacterial candidate to combat the bacterial resistance.